Lo amixer: ¿racismo virtual? - Cerna Aragón, Diego Alonso (2012)
The objective of this document is to provide a contextualization of “amixer” concept inside the academic and media discussion. In the same way, this document tries to provide a new approach to the peruvian virtual racism using theoretical categories taken from zizekian psychoanalysis.